Caldera’s Breathing: Poroelastic Ground Deformation at Campi Flegrei (Italy) - Todesco, Micol (Frontiers in Earth Science, 2021)
Ground deformation at Campi Flegrei has fuelled a long-term scientific debate about its driving mechanism and its significance in hazard assessment. In an active volcanic system hosting a wide hydrothermal circulation, both magmatic and hydrothermal fluids could be responsible, to variable degrees, for the observed ground displacement. Fast and large uplifts are commonly interpreted as magma intrusion, while minor, slower displacement can be related to shallower sources. This work focuses on the deformation history of the last 35 years and shows that ground deformation measured at Campi Flegrei since 1985 is consistent with a poroelastic response of a shallow hydrothermal system to changes in pore pressure and fluid content. The extensive literature available for Campi Flegrei allows constraining system geometry, properties, and conditions. Changes in pore pressure and fluid content necessary to cause the observed deformation can then be calculated based on the linear theory of poroelasticity. The predicted pore pressure evolution and fluid fluxes are plausible and consistent with available measurements and independent estimates.